William Wordsworth’s Definition of Poverty - Snow, Heidi (Romanticism and Victorianism on the Net, 2009)
A close examination of Dorothy Wordsworth and William Wordsworth’s writing indicates that they considered themselves as living in poverty for some years before their case was settled with Lord Lowther. Both their material circumstances and contemporary definitions of poverty led them to identify themselves as “poor.” This article examines that self-identification and its evidence in their writings. Finally, William Wordsworth’s poem, “Last of the Flock,” indicates that he rejected a narrow parish view of poverty for a wider view that included the right to own some property.